A device for performing automated balloon catheter inflation ischemia studies. - Silas J Leavesley; Whitley Ledkins; Petra Rocic (PLoS ONE)
Coronary collateral growth (arteriogenesis) is a physiological adaptive response to transient and repetitive occlusion of major coronary arteries in which small arterioles (native collaterals) with minimal to no blood flow remodel into larger conduit arteries capable of supplying adequate perfusion to tissue distal to the site of occlusion. The ability to reliably and reproducibly mimic transient, repetitive coronary artery occlusion (ischemia) in animal models is critical to the development of therapies to restore coronary collateral development in type II diabetes and the metabolic syndrome. Current animal models for repetitive coronary artery occlusion implement a pneumatic occluder (balloon) that is secured onto the surface of the heart with the suture, which is inflated manually, via a catheter connected to syringe, to effect occlusion of the left anterior descending coronary artery (LAD). This method, although effective, presents complications in terms of reproducibility and practicality. To address these limitations, we have designed a device for automated, transient inflation of balloon catheters in coronary artery occlusion models. This device allows repeated, consistent inflation (to either specified pressure or volume) and the capability for implementing very complex, month-long protocols. This system has significantly increased the reproducibility of coronary collateral growth studies in our laboratory, resulting in a significant decrease in the numbers of animals needed to complete each study while relieving laboratory personnel from the burden of extra working hours and enabling us to continue studies over periods when we previously could not. In this paper, we present all details necessary for construction and operation of the inflator. In addition, all of the components for this device are commercially available and economical (Table S1). It is our hope that the adoption of automated balloon catheter inflation protocols will improve the experimental reliability of transient ischemia studies at many research institutions.